Analisis Metode Permainan Sosial untuk Pembelajaran IPS di Sekolah Dasar/Madrasah Ibtidaiyah - Syaikhudin, Ahmad (Taallum: Jurnal Pendidikan Islam, 2013)
Education is a deliberate effort to improve learnerâs personality through the mastery of knowledge, affection, and good behavior. To improve the quality of education, it is important to develop method and strategies of teaching subject matter including social sciences subject matter. Some social games are worth doing for teaching such subject matter. This article is intended to review each game strategy within the confine of classic and modern theory of social game. Teacher plays important role in the success of implementation of method.